Answer:
|3x + 4 | + 6
Step-by-step explanation:
(f+g)(x)= f(x) + g(x)
= |3x+4| + 2 + 4
= | 3x + 4 | + 6
Answer:
Not entirely positive of about the answers, but all of the values would equal 15
First Y = 5
First X = 15
Second X = -3
Answer:
A.
Step-by-step explanation:
B. y = 0x =0, or y =0, y is a constant.
A. y = 0.5x, in general from y = kx. It is the direct variation.
Answer:
Slope is 3/8
Step-by-step explanation:
( -1 + 4)/ (5 + 3)
3/ 8
Answer:
m1=45
m1=88
m2=42
m3=113
Step-by-step explanation: